Jin-Zhen oral liquid for pediatric coronavirus disease (COVID-19): A randomly controlled, open-label, and non-inferiority trial at multiple clinical centers - Dong, Qian; Qiao, Hongmei; Jiang, Huiyi; Liu, Lixiao; Ge, Yanling; Zong, Fang-Jiao; Li, Yanan; Dong, Bingzi; Hu, Sujuan; Meng, Dongmei; Jin, Rong; Wang, Xiangshi; et al. (Frontiers in Pharmacology, 2023)
BACKGROUND: As the coronavirus disease 2019 (COVID-19) pandemic progressed, especially with the emergence of the Omicron variant, the proportion of infected children and adolescents increased significantly. The efficacy and safety of Jin-Zhen Oral Liquid in the treatment of pediatric COVID-19 are unclear. METHODS: We conducted a randomized controlled, open-label, multicenter, non-inferiority clinical study involving hospitalized children with mild to moderate COVID-19. Children eligible for enrollment were randomly assigned in a 1:1 ratio to Jin-Zhen Oral Liquid (the treatment group) and Jinhua Qinggan Granules (the positive control group). The primary efficacy endpoint was the time to first negative viral testing. The secondary endpoints were the time and rate of major symptoms disappearance, duration of hospitalization, and the proportion of symptoms changed from asymptomatic or mild to moderate or severe/critical illness. The safety end points of any adverse events were observed. RESULTS: A total of 240 child patients were assigned randomly into the Jin-Zhen Oral Liquid (117 patients) and Jinhua Qinggan Granules (123 patients) groups. There was no significant difference of the baselines in terms of the clinical characteristics and initial symptoms between the two groups. After 14-day administration, the time to first negative viral testing in the Jin-Zhen group (median 6.0 days, 95% CI 5.0-6.0) was significantly shorter compared with the positive control Jinhua Qinggan Granules group (median 7.0 days, 95% CI 7.0-8.0). The time and rate of disappearance of major clinical symptoms were comparable to the positive control. The hospitalization duration was significantly shortened in the Jin-zhen Oral Liquid group. No adverse events were observed in the Jin-Zhen Oral Liquid treatment group (0.0%) while 1 patient with adverse events occurred in the positive control Jinhua Qinggan granules group (0.8%). CONCLUSION: Jin-Zhen Oral Liquid is safe and effective in the treatment of mild to medium COVID-19 in children. It is noninferior to Jinhua Qinggan granules in shortening the time to first negative viral testing, the time and rate of major clinical symptoms disappearance, and the hospitalization duration. The results suggest that Jin-Zhen Oral Liquid can be a recommended drug for treatment of pediatric COVID-19 patients.